2009
DOI: 10.1111/j.1399-3038.2009.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and glutathione level in children with asthma bronchiale: Effect of antiasthmatic therapy

Abstract: When the production of reactive oxygen species (ROS) exceeds the capacity of antioxidant defences, a condition known as oxidative stress occurs and it has been implicated in many pathological conditions including asthma. Interaction of ROS with DNA may result in mutagenic oxidative base modifications such as 8-hydroxydeoxyguanosine (8-oxo-dGuo) and DNA strand breaks. Reduced glutathione (GSH) serves as a powerful antioxidant against harmful effects of ROS. The aim of this study was to describe DNA damage as le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In our study, TAS levels were decreased compared with the control group, probably because of being used to balance oxidative stress. In another study, Hasbal et al [23 ]reported high DNA strand breaks and reduced glutathione levels in pediatric asthmatics compared with healthy controls. After the treatment, that contained ICS + LT receptor antagonist + systemic antihistaminic and inhaled β 2 -mimetic if necessary, the DNA strand breaks were found to have decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, TAS levels were decreased compared with the control group, probably because of being used to balance oxidative stress. In another study, Hasbal et al [23 ]reported high DNA strand breaks and reduced glutathione levels in pediatric asthmatics compared with healthy controls. After the treatment, that contained ICS + LT receptor antagonist + systemic antihistaminic and inhaled β 2 -mimetic if necessary, the DNA strand breaks were found to have decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, although there are some reports that show that allergic diseases can cause increased DNA damage, there are only a few reports assessing if treatment alters such damage [22,23,24]. Apart from 1 in vitro study, there is no information on whether montelukast monotherapy can overcome oxidative stress in asthma [25].…”
Section: Introductionmentioning
confidence: 99%
“…DNA binding inhibitors of NF-κB such as GCs do not significantly influence the cellular antioxidant enzyme levels (Hasbal et al, 2010;Rahman et al, 1999). Additionally, as revealed by Mattson et al (2000), not the classical p50:p65 dimers, but rather RelB:p52 dimers may be responsible for antioxidant enzyme induction (Perkins, 2007;Perkins and Gilmore, 2006).…”
Section: Nf-κb and Melatoninmentioning
confidence: 94%
“…GSH levels were determined using the method by Beutler et al, as described before [17]. The activity of enzymes GPx and SOD were measured using spectrophotometric kits (Randox, UK).…”
Section: Methodsmentioning
confidence: 99%